Enzyme kinetics modelling approach to evaluate the impact of high CO2 and super-atmospheric O2 concentrations on respiration rate of pomegranate arils. Issue 4 (2nd October 2017) - Belay, Zinash A.; Caleb, Oluwafemi J.; Opara, Umezuruike Linus
ABSTRACT: Super-atmospheric O2 has been shown to affect respiration rate (RR), but no model describing its effect on RR for pomegranate arils has been reported. This study investigated the effects of four different gas compositions (5 kPa O2, 10 kPa CO2 and 85 kPa N2 ; 10 kPa O2, 5 kPa CO2 and 85 kPa N2 ; 70 kPa O2, 10 kPa CO2 and 20 kPa N2 ; and air) on RR of pomegranate arils (cv. Wonderful) stored at 5°C. Michaelis–Menten enzyme kinetics models were used to investigate the effect of CO2 inhibition on O2 consumption rate. Respiratory quotient was used to determine fermentation threshold. The O2 consumption rate increased from 0.87 to 2.81 mL/kg h, with increase in O2 concentration from 5 kPa to 70 kPa. All enzyme kinetics model parameters adequately described the influence of gas concentration on aril RR with correlation coefficient ( R 2 adj = 81–91%).